Virtual Reality as a Media For Japanese Cave Exploration - Akay, Yuri V.; Mapaly, Heilbert Armando (Jurnal Teknik Informatika, 2024)
Kawangkoan is an area located in North Sulawesi, Indonesia, presenting stunning natural beauty while storing extraordinary historical and cultural richness. The Japanese Cave is a striking historical heritage in Kawangkoan and is also one of the tourist attractions in Minahasa Regency. But unfortunately not everyone dares to visit physically for security reasons. In the world of tourism and history, Virtual Reality can be used as a medium to explore historical tourist attractions without having to visit physically and can also add information from a historical tourist attraction. The purpose of this study is to develop a Virtual Reality application that can be used as a medium for Japanese Cave Exploration in Kawangkoan. The method used in designing this system is MDLC. The results of this study are to produce a VR application that can be used as a medium for Japanese Cave exploration that runs on Android smartphones.